Time to Review and Revise the Peer Review Process: A Critique - Sharma, Pawan; Singh, Swarndeep; Balhara, Yatan Pal Singh; Subedi, Sandip (Journal of Psychiatrists' Association of Nepal, 2021)
Biomedical publishing is valuable as it is the process of disseminating novel and valuable scientific information. The publication of an article relies mainly on the peer review process that has been regarded as a gold standard for a long time. Despite being successful, the process has had a fair share of criticism. There is a need for considering some reforms in terms of transparency, accountability, and quality for this process. In this review, we aim to bring forward some criticism and provide recommendations for improvement of the peer-review process.